Preoperative magnetic resonance imaging-radiomics in cervical cancer: a systematic review and meta-analysis - Wu, Linyong; Li, Songhua; Li, Shaofeng; Lin, Yan; Wei, Dayou (Frontiers in Oncology, 2024)
Background: The purpose of this systematic review and meta-analysis is to evaluate the potential significance of radiomics, derived from preoperative magnetic resonance imaging (MRI), in detecting deep stromal invasion (DOI), lymphatic vascular space invasion (LVSI) and lymph node metastasis (LNM) in cervical cancer (CC). Methods: A rigorous and systematic evaluation was conducted on radiomics studies pertaining to CC, published in the PubMed database prior to March 2024. The area under the curve (AUC), sensitivity, and specificity of each study were separately extracted to evaluate the performance of preoperative MRI radiomics in predicting DOI, LVSI, and LNM of CC. Results: A total of 4, 7, and 13 studies were included in the meta-analysis for DOI, LVSI, and LNM, with 839, 1263, and 2182 CC patients, respectively. The overall AUC, sensitivity, and specificity of preoperative MRI models in predicting DOI, LVSI, and LNM were 0.90, 0.83 (95% confidence interval [CI], 0.75-0.89) and 0.83 (95% CI, 0.74-0.90); 0.85, 0.85 (95% CI, 0.73-0.86) and 0.75 (95% CI, 0.66-0.82); 0.86, 0.80 (95% CI, 0.75-0.84) and 0.80 (95% CI, 0.77-0.83), respectively. Notably, radiomics-clinical models exhibited superior performance compared to either radiomics models or clinical models alone. Conclusion: MRI radiomics has demonstrated considerable potential in predicting DOI, LVSI, and LNM in CC, positioning it as a valuable tool for preoperative precision evaluation in CC patients.